Community Structure of Gastrpods in Mokupa Beach, Sub-district of Tobariri,Minahasa Regency, North Sulawesi Province - Alinaung F. Firgonitha; Anneke V. Lohoo; Alex D. Kambey (Jurnal Ilmiah PLATAX, 2015)
Ecologically intertidal mollusk has important role in the food chains. As a filter feeder, mollusk is also known as a food source for other marine organisms. The intertidal zone is known as the smallest area in the ocean basin (Nybakken, 1992). This zone is a narrow edge cover only few square meters and position between low tide mark (LTM) and high tide mark (HTM). The study was conducted in Mokupa beach waters, Tombariri sub-district, Minahasa Regency. Coastal area of Mokupa village represent typical tropical ecosystem such as coral reef, seagrass bed and mangrove belt. As many as 45 species in 134 total individuals were recorded during the study. The density of gastropods collected is 4.4667 individual/m2 while density for gastropods species Littoraria scabra Linne was 0.4000 individual/m2 and in term of relative density is 9.834 % and thus considered the highest. Species diversity index of this species is H’ = 2.37594. Keywords: mollusk, diversity, dominance   A B S T R A K   Secara ekologis Moluska yang menempati daerah intertidal memiliki peranan yang besar kaitannya dengan rantai makanan. Karena di samping sebagai filter feeder, moluska juga merupakan makanan bagi biota lainnya. Zona intertidal (pasang-surut) merupakan daerah terkecil dari semua daerah yang terdapat di samudera dunia (Nybakken, 1992). Zona ini merupakan pinggiran yang sempit sekali, hanya beberapa meter luasnya, terletak di antara air pasang tinggi dan air surut rendah. Penelitian ini dilaksanakan di perairan pantai Mokupa Kecamatan Tombariri Kabupaten Minahasa. Daerah pantai Desa Mokupa merupakan daerah yang lokasinya terdapat ekosistem yang khas di daerah tropis yaitu terumbu karang, padang lamun, dan hutan mangrove. Diperoleh sebanyak 45 spesies dan berjumlah 134 individu. Kepadatan rata-rata organisme Gastropoda diperoleh 4,4667 indv/m2 , dengan  kepadatan spesies tertinggi 0,4000 indv/m2 (Littoraria scabra Linne), dengan Kepadatan relative  adalah 9,834 %.Keanekaragaman spesies diperoleh nilai (H’= 2.37594)   Kata Kunci : Komunitas, keanekaragaman, dominasi 1Mahasiswa Program Studi MSP FPIK-UNSRAT 2Staf pengajar Fakultas Perikanan dan Ilmu Kelautan Universitas Sam Ratulangi